Variations in Electric Switching and Transverse Resistance of GeTe/ Sb2Te3 Superlattices at Elevated Temperature Studied by Conductive Scanning Probe Microscopy - Bolotov, Leonid; Saito, Yuta; Tada, Tetsuya; Tominaga, Junji (MRS advances, 2018)
Temperature-dependent variations in electric switching and transverse resistance of phase-change [(GeTe) 2 (Sb 2 Te 3 )] n (n=4 and 8) chalcogenide superlattice (CSL) films were studied using conductive scanning probe microscopy (SPM). Three temperature regions with different electric transport properties were recognized in point current-voltage (I-V) spectra and the surface potential maps measured with tantalum and platinum-coated SPM cantilevers. At around 80°C the switching voltage decreased abruptly from ∼2 V to 0.5 V and the thermal coefficient of resistance changes its sign, indicating different carrier transport mechanisms. The observed changes correlated with decrease in the surface potential by ∼150 meV from 25 to 150°C. The results were ascribed to an opening of the CSL electronic band gap near the Fermi energy caused by thermal stress, which led to the transition from a Dirac-like semimetal to a narrow-gap semiconductor.